Effect of Pressure on the Structural and Mechanical Properties of Cubic Silicon Carbide Reinforced with Aluminum and Magnesium - Adel Bandar Alruqi; Nicholas O. Ongwen (Aerospace)
Ranging from the most demanding technical applications to soft, extremely ductile wrapping foil, aluminum is one of the most versatile and reasonably priced metallic materials. These are attributable to the unique blend of features that it provides, together with its alloys, owing to its lightweight, and some of its alloys have higher strengths than that of structural steel. However, it is expected that the demand for aluminum will quadruple within the next 10 years, and as a result, the aerospace industry is increasingly turning to recycled alloys to fulfill its high demand. This study uses the ab initio method, implemented in the quantum espresso code, to examine the influence of pressure on the structural and mechanical properties of cubic silicon carbide alloyed with aluminum (Al) and magnesium (Mg). The study is motivated by the aerospace industry’s growing need for sustainable materials. Some of the carbon atoms were swapped out for Al or Mg or both (co-doping) atoms in order to create the alloys. The results demonstrated that the application of pressure significantly influences both the structural and mechanical properties of the alloys, making them a promising option for the construction of environmentally friendly aircraft components.